2017
DOI: 10.1111/bph.13841
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of transmembrane member 16A calcium‐activated chloride channels by natural flavonoids contributes to flavonoid anticancer effects

Abstract: This study demonstrates that flavonoids inhibit TMEM16A currents and suggests that flavonoids could have anticancer effects via this mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Several studies have confirmed that T16Ainh-A01 and CaCCinh-A01 exert their inhibitory effects in a dose-dependent manner [18,19,27,28]. T16Ainh-A01 (10 µM) strongly inhibits TMEM16A-mediated iodide influx and completely blocks CaCC conductance in salivary gland cells.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have confirmed that T16Ainh-A01 and CaCCinh-A01 exert their inhibitory effects in a dose-dependent manner [18,19,27,28]. T16Ainh-A01 (10 µM) strongly inhibits TMEM16A-mediated iodide influx and completely blocks CaCC conductance in salivary gland cells.…”
Section: Discussionmentioning
confidence: 92%
“…Inhibitors of TMEM16A also comprise chemically synthesized compounds and the components from natural products. Some natural products have been identified as inhibitors of TMEM16A, including tannic acid and related gallotannins (Namkung, Thiagarajah, Phuan, & Verkman, ), the major component of clove oil, eugenol (4‐allyl‐2‐methoxyphenol; Yao et al, ), shikonin (Jiang, Yu, Yang, & Ma, ), dehydroandrographolide (DP) (Sui et al, ), and flavonoid compounds (luteolin, galangin, quercetin, and fisetin; X. Zhang et al, ). These compounds were found to have the ability to resist diarrhea or inhibit proliferation, migration, and invasion of cancer cells.…”
Section: Tmem16a Modulators (Summarized In Table )mentioning
confidence: 99%
“…dehydroandrographolide (DP)(Sui et al, 2015), and flavonoid compounds(luteolin, galangin, quercetin, and fisetin;X. Zhang et al, 2017).…”
mentioning
confidence: 99%
“…Some TMEM16A inhibitors have been identified. One class belongs to natural product TMEM16A inhibitors, including tannic acid, and related gallotannins, 8 eugenol (4-allyl-2-methoxyphenol), 9 shikonin, 10 dehydroandrographolide (DP), 11 flavonoid compounds (luteolin, galangin, quercetin, and fisetin), 12 and matrine. 13 The other class is consists of chemically synthesized TMEM16A inhibitors, including niflumicacid (NFA), 14 CaCC inh -A01, 15 T16A inh -A01, 16 MONNA (N-((4-methoxy)-2-naphthyl)-5nitroanthranilic acid), 17 9-phenanthrol, 18 substituted 2-acylaminocycloalkylthiophene-3-carboxylic acid arylamides (AACTs).…”
Section: Introductionmentioning
confidence: 99%